(917) The Discriminant Function Analysis تحليل دالة التمييز - Moharram W. Mahmoud (INP, 2024)
Discriminant function analysis was first introduced by R.A. Fisher in 1936, leading to a new line of research that uses a set of multiple measurements to provide a linear discriminant function that best discriminates between two or more populations. This note addresses the simple case of discriminant function analysis with only two groups.